BOOK TAX DIFFERENCES, KEBIJAKAN HUTANG DAN PROFITABILITAS DAMPAKNYA TERHADAP PERUBAHAN KEUNTUNGAN PADA PERBANKAN UMUM SYARIAH DIINDONESIA - Busra Busra; cut ridha zarina; Mukhlisul Mujahid; nurmila dewi; yulianisah yulianisah; syarifudin syarifudin (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2023)
This study has the aim of testing the effect of the model partially or simultaneously, namely changes in the profits of Sharia General Banking in Indonesia which are thought to be influenced by booktax differences, debt policies and profitability. The population is all sharia commercial banks operating in Indonesia, using purposive sampling ten samples were selected. The classical assumption test is carried out first before testing the model, and the results are that the model being tested is free from the classical assumption problem. By using panel data regression test, it is obtained that simultaneously all variables have a significant effect on changes in the profits of Islamic banking in Indonesia. While the partial test shows that there is a permanent difference and debt policy has a negative and significant effect on changes in profits, temporary differences and profitability have a positive and significant effect on changes in profits.